Knowledge, Attitude, and Willingness Toward Kidney Donation Among Health Sciences Students at King Saud Bin Abdulaziz University - Raghad Sharaan; Sara Alsulami; Raneem Arab; Ghida Alzeair; Nadia Elamin; Basim Alsaywid; Basim Alsaywid; Basim Alsaywid; Miltiadis Lytras; Miltiadis Lytras (Frontiers Media S.A., 2021)
Background: End-stage renal disease, as one of the most serious and major health problems, does not have many treatment options available. One of the best treatment modalities used to cure this debilitating disease is kidney transplantation. However, with the continuous increase in number of patients diagnosed with it, there is not enough supply of the organ. The aim of our study is to assess knowledge about, attitude toward, and willingness to donate kidney among health science students at King Saud bin Abdulaziz University in comparison to the general population in Jeddah and to investigate the factors that play a role on their willingness.Methods: This is an observational, analytical, cross-sectional study design conducted in 2019. Two target populations were included: King Saud bin Abdulaziz University for Health Sciences students and the general population in Jeddah. Data were collected via a self-administered, close-ended, structured, and previously validated questionnaire that contained 39 items divided into four sections. SPSS program version 22 was used in data analysis.Results: Out of 685 surveyed participants, 179 (26.1%) were willing to donate their kidney, with students showing a higher rate of willingness (N = 101; 32.3%) than the general population (N = 78; 21%). However, only 46 (6.7%) out of the total population hold an organ donor card. In bivariate analysis, it was found that knowledge significantly associated with a higher rate of willingness among the student population than the general population, while positive beliefs were associated with increased willingness in the general population than students. Positive attitude appeared to play a role in higher willingness among the general population and student population.Conclusion: There is a low perception of awareness regarding kidney donation in both populations of this study. The willingness rate of health science students at King Saud bin Abdulaziz University and the general population was low when compared with other studies conducted internationally.